EGO - Where User Modeling Meets Identity Management - Abramowicz, Witold; Filipowska, Agata; Dzikowski, Jakub; Kalisz, Paweł; Małyszko, Jacek; Werno, Łukasz (EGO - na pograniczu modelowania użytkownika i zarządzania tożsamością, 2010)
Current identity management and user modeling systems suffer from certain limitations. Although, theoretically, they have similar goals: to represent a user and to support him while carrying out certain activities, there is a clear gap between them in means of aspects of users' activity, which they represent. This paper addresses this issue, proposing a system, which aims at incorporating strengths of both types of systems to provide a single, unified method of representation of users in the Web. Description of the system includes functional analysis, system architecture, identity life cycle scheme and more.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 119, s. 11-20
Keywords: identity management; user modeling; adaptive system; personalization